Managing Archaeology. - Carman, John.
1 online resource (277 pages)
Keywords: Effective management is becoming increasingly important in all aspects of archaeology. Archaeologists must manage the artefacts thay deal with, their funding, ancient sites, as well as the practice of archaeology itself. Managing Archaeology is a collecton of outstanding papers from experts involved in these many areas. The contributors focus on the principles and practice of management in the 1990s, covering such crucial aeas as the management of contract and field archaeology, heritage management, marketing, law and information technology. The resulting volume is important and informative reading for archaeologists and heritage managers, as well as planners, policy makers and environmental consultants.